Sn4+complexation with sulfonated-carbon dots in pursuit of enhanced fluorescence and singlet oxygen quantum yield - Luo, Qinghua; Ding, Haizhen; Hu, Xiaolong; Xu, Jiahui; Sadat, Anwar; Xu, Mingsheng; Primo, Fernando Lucas [UNESP]; Tedesco, Antonio Claudio; Zhang, Haiyuan; Bi, Hong (Royal Society of Chemistry (RSC), 2020)
Here we report a novel strategy to crosslink the surface of sulfonated-carbon dots (S-CDs) by complexing SnCl4with sulfonate groups (-SO3-) on the CDs in aqueous solution. The S-CDs show an average photoluminescence (PL) quantum yield of 21% and a mean diameter of 3.8 nm. After being complexed with Sn4+, the as-obtained Sn@S-CDs present a reduced size of 1.8 nm and a higher PL quantum yield of 32%. More interestingly, the Sn@S-CDs show an enhanced singlet oxygen (1O2) quantum yield as high as 37% compared to that of the S-CDs (27%). In the HepG2 cell line as a model, the Sn@S-CDs exhibit a remarkable cell imaging effect andin vitroPDT efficiency. Therefore, our study proposes a simple but effective cross-linking strategy to synthesize CDs incorporated with metal ions, for the purpose of achieving an enhanced fluorescence intensity and a higher1O2quantum yield.